Trichoderma viride Laccase Plays a Crucial Role in Defense Mechanism against Antagonistic Organisms - Divya, Lakshmanan; Sadasivan, C. (Frontiers in Microbiology, 2016)
Fungal laccases are involved in a variety of physiological functions such as delignification, morphogenesis and parasitism. In addition to these functions, we suggest that fungal laccases are involved in defense mechanisms. When the laccase secreting Trichoderma viride was grown in the presence of a range of microorganisms including bacteria and fungi, laccase secretion was enhanced in response to antagonistic organisms alone. In addition, growth of antagonistic microbes was restricted by the secreting fungi. Besides, our study for the first time shows the inability of the secreting fungi (T.viride) to compete with antagonistic organism when laccase activity is inhibited, further emphasizing its involvement in rendering a survival advantage to the secreting organism. When laccase inhibitor was added to the media, the zone of inhibition exerted by the antagonist organism was more pronounced and consequently growth of T. viride was significantly restricted. Based on these observations we accentuate that, laccase plays an important role in defense mechanism and provides endurance to the organism when encountered with an antagonistic organism in its surrounding.